Pareidolia in infants. - Masaharu Kato; Ryoko Mugitani (PLoS ONE, 2015)
Faces convey primal information for our social life. This information is so primal that we sometimes find faces in non-face objects. Such illusory perception is called pareidolia. In this study, using infants' orientation behavior toward a sound source, we demonstrated that infants also perceive pareidolic faces. An image formed by four blobs and an outline was shown to infants with or without pure tones, and the time they spent looking at each blob was compared. Since the mouth is the unique sound source in a face and the literature has shown that infants older than 6 months already have sound-mouth association, increased looking time towards the bottom blob (pareidolic mouth area) during sound presentation indicated that they illusorily perceive a face in the image. Infants aged 10 and 12 months looked longer at the bottom blob under the upright-image condition, whereas no differences in looking time were observed for any blob under the inverted-image condition. However, 8-month-olds did not show any difference in looking time under both the upright and inverted conditions, suggesting that the perception of pareidolic faces, through sound association, comes to develop at around 8 to 10 months after birth.